1999
DOI: 10.1093/tropej/45.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for hospitalization due to abortion and pregnancy termination

Abstract: The aim of this study was to identify the reasons for hospitalization associated with abortion and pregnancy termination among women attending the Maternity Unit of IMIP, Recife, Brazil. In a case-control study, 230 women who were hospitalized consecutively between August 1994 and June 1995 due to causes related to pregnancy termination or abortion were chosen as cases. Four controls per case were selected randomly out of a total of 920 women who delivered at the same hospital. For each potential cause conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…This finding is supported by de Souza et al [25] who found that the staphylococcal adherence to lower reproductive tract epithelia was mediated by cell surface mucin. In addition to mucin and GAGs, Sylvester et al [26] and Walz et al [27] stated that glycoconjugates on the mammalian cell membrane may act as receptors for pathogenic microorganisms.…”
Section: Discussionsupporting
confidence: 70%
“…This finding is supported by de Souza et al [25] who found that the staphylococcal adherence to lower reproductive tract epithelia was mediated by cell surface mucin. In addition to mucin and GAGs, Sylvester et al [26] and Walz et al [27] stated that glycoconjugates on the mammalian cell membrane may act as receptors for pathogenic microorganisms.…”
Section: Discussionsupporting
confidence: 70%